Psychological types and their effect on the use of accounting information: a study about managers of small enterprises - Cardoso, Ricardo Lopes (Anais do Congresso Brasileiro de Custos - ABC)
The objective of this research is to investigate if there is a relation between the psychological profile of the entrepreneurs of small enterprises and the use of accounting information in a decision making. This study is based on Jung’s (1921) works, which inspires the typologies used in this research, the MBTI - Myers-Briggs Type Indicator. For the accomplishment of this research, we considered the answers of 80 entrepreneurs of small enterprises. The results show that there is no relation between the psychological profile and the use of accounting information. Notwithstanding this fact, we hereby observe that the objective of the use of the information is mostly for legal requirements and a very small fraction for management purposes. Emphasizing that the entrepreneur’s profile is determined by the psychological type SJ (Sensorial and Judgment), and this is the one that most uses accounting information.